Platelets with wings: the maturation of Drosophila integrin biology. - Brower, D.L. (Current Opinion in Cell Biology, 2003)
The integrin family of cell surface receptors is strongly conserved in metazoans, making simple invertebrate genetic systems valuable contributors to understanding integrin function. The Drosophila integrins have long served as a paradigm for genetic studies of adhesion proteins during development. Currently, Drosophila experiments are exploring more general aspects of integrin biology. Genetic screens are identifying proteins involved in integrin adhesion complexes and signaling, and structures such as embryonic muscle attachments can be manipulated experimentally to dissect the functions of cytoplasmic components of integrin adhesion sites in whole animals. Drosophila also is beginning to yield some insights into integrin heterodimer structure and function.